Valuation of a construction company, pt. Xyz – a case study - Lande, Dennis Aditya; Murtaqi, Isrochmani (Journal of Business and Management, 2020)
Abstract. PT. XYZ is a company that move in construction sector. PT. XYZ is not a publicly listed company and hasn’t planning on going IPO yet. The shares are owned by private investors. Recently, PT. XYZ is in talks with a potential shareholder to invest in the company. Existing shareholder of PT. XYZ is willing to give up a maximum of 20% dilution from the new share composition by issuing new shares. By doing valuation of PT. XYZ, we can calculate how much worth of 20% PT. XYZ share dilution to help PT. XYZ determine it price. The projection growth of PT. XYZ will consider the COVID-19 outbreak. Valuation of PT. XYZ will be using DCF approach. From DCF valuation, PT. XYZ intrinsic value is IDR 345,141,295,887 which is 1.83x their book value. Current number of share of PT. XYZ is 25,678 shares, which will become 32,098 shares after dilution. There will be 6,420 new shares that will be subscribed by new investor.Keywords: Construction Industry, Valuation, Discounted Cash Flow